Synthesis and degradation of phosphoenolpyruvate carboxylase in rat liver and adipose tissue. Changes during a starvation–re-feeding cycle - M F Hopgood; F J Ballard; Lea Reshef; Richard W. Hanson (1973)
A specific antibody against liver cytosol phosphoenolpyruvate carboxylase (EC 4.1.1.32) was used to isolate the enzyme from liver and adipose tissue. With this technique we have shown that phosphoenolpyruvate carboxylase synthesis in starved rats accounts for 3% of the total synthesis of cytosol protein in each tissue. Re-feeding starved animals decreases this relative rate of phosphoenolpyruvate carboxylase synthesis to 0.2% and 1% respectively in liver and adipose tissue, and the activity of the enzyme in each tissue is decreased to 25% of the starvation value. An additional starvation period is accompanied by an increased rate of enzyme synthesis, but the response to starvation is considerably slower than that caused by re-feeding. The degradation rate of phosphoenolpyruvate carboxylase is also subject to regulation. Thus re-feeding starved animals decreases the half-life of the enzyme in liver from 13h to 5.2h, but the rapid rate of degradation is maintained at least during the first 20h of subsequent starvation. Only slight changes in the degradation rate of phosphoenolpyruvate carboxylase are found in adipose tissue. We conclude that the large alterations in the rate of enzyme synthesis during a starvation-re-feeding cycle are the major cause of fluctuations in activity.